The Effect of Education by Visual Compact Disc on Two time- period of Pre-operation Anxiety of Patients who were Candidates for Coronary Artery Bypass Graft (CABG) - L. Moemeni; A. Najaf Yarandi; F. Kabiri; H. Haghani; C. Darabian (Iran University of Medical Sciences, 2006)
Today, arthrosclerosis of coronary arteries is one of the most common life threatening diseases in patients. In fact, Coronary Artery Bypass (CABG) is high risk surgery in both developed and developing countries and heart is a vital organ that is susceptible for any disorders which could be life theatening, because of undergoing CABG patients with high anxiety and stress. Due to surgery anxiety, heart rate, cardiac output and oxygen demand will rise. Then any attempt to decrease patients' preoperational anxiety would be beneficial. One of the efforts to decrease the anxiety level is patient education. There are different viewpoints about educational methods in the literature. This study was a randomized clinical trial with the purpose of determination of the effect of education with visual compact disc (VCD) on the patients' anxiety at the first day and sixth day of admission. Sixty patients were included, 30 were assigned into experimental group and 30 subjects into control group. Sampling method was consecutive. The Spielbergers' questionnaire was used for data collection pre and post educational intervention. The result indicated that the late trait anxiety level significantly decreased in the experimental group compared to the control group at the 6th day before CABG (t=3.79, P=0.001) (t=4.53, P=0.00) respectively. According to the study results, use of visual information by VCD at sixth day before surgery was more effective in clinical setting that the first day. Therefore, nurses can use this educational cost-effective beneficial intervention, for reducing the patients' anxiety .